From Usul Fiqh to Legal Pluralism: An Autoethnography of Islamic Legal Thought - Salim GP, M. Arskal (Mazahib, 2020)
This article seeks to introduce an autoethnography as a method in studying Islamic law. Through an autoethnography, a scholar could share a unique and subjective experience, which would not only contribute to the understanding of social phenomenon but also reflect on possible different situations upon knowing the reality. It not only makes a sequence of events and their interpretation, but it also asks readers to emotionally ‘relive’ the events with the writer of autoethnography. This article uncovers processes and dynamics of my own thought in approaching and comprehending law in Islam including topics such as usul fiqh and legal pluralism. It discloses the development of my research interest and scope, both nationally and internationally in the past three decades. The article argues that knowledge is not necessarily produced by research work. In fact, personal narratives are considered scientific in that they could contribute knowledge to what we know about the world in which we live. And, last but not least, personal stories are valuable if they could: 1) provide a legitimate claim or justification, 2) offer something new to learn, and 3) help other people cope with or better understand world issues.Keywords: autoethnography, Islamic law, legal pluralism, usul fiqh.